1962
DOI: 10.1002/pol.1962.1205816627
|View full text |Cite
|
Sign up to set email alerts
|

γ‐radiation of p‐substituted polystyrenes

Abstract: The electronic environment about the main chain atoms in polystyrenes has been varied systematically by introducing electronegative or electropositive substituents (H3C, CH3O, Br, Cl, NC, and O2N groups) in the p‐position of the ring. Energy yields for γ‐initiated H2 formation and crosslinking, both a measure of the radiation sensitivity of the backbone, were determined above and below Tg from (1) mass spectrometric examination of the decomposition gases and (2) molecular weight changes. For most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Before answering this question, let us review the reported data first. The G(x) values were found to be within a range of 0.03 to 0.05 [15,24,25], when polystyrene was subjected to 1.25 MeV (average) '%oy-rays (0.2 eV/nm), 275 MeV Ne" (370 eV/nm), and 180 MeV Ar8+ (2260 eV/nm) as summarized in Table 11 In most experiments, G(x) values were derived from the molecular weight distributions determined by gel permeation chromatography (GPC) [ 15,261 or viscosity measurements [24] after dissolving irradiated polymers in a solvent. This requires polymers to be still soluble after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Before answering this question, let us review the reported data first. The G(x) values were found to be within a range of 0.03 to 0.05 [15,24,25], when polystyrene was subjected to 1.25 MeV (average) '%oy-rays (0.2 eV/nm), 275 MeV Ne" (370 eV/nm), and 180 MeV Ar8+ (2260 eV/nm) as summarized in Table 11 In most experiments, G(x) values were derived from the molecular weight distributions determined by gel permeation chromatography (GPC) [ 15,261 or viscosity measurements [24] after dissolving irradiated polymers in a solvent. This requires polymers to be still soluble after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of aromatic side groups in polymers has been shown to increase the polymer's radiation resistance due to its delocalized π-electron structure, crosslinking has been shown to occur. 14,15 As seen in Figure 11, a corresponding change in G' upon irradiation can be seen, due to increased crosslinking. Although the current results indicate that the crosslink density of an irradiated polymer increases with dose, this apparently has no effect on the ultimate amount of crystallinity that occurs.…”
Section: Resultsmentioning
confidence: 91%
“…Another important aspect of fullerene nanowires is its extremely high cross-linking efficiency. The G value, defined by the number of chemical reactions per 100 eV absorbed energy used in radiation chemistry, is as large as 55 (100 eV) -1 , 21) more than two orders of magnitude higher than those of polymers (0.1 ~ 1 (100 eV) -1 ), 30) and even higher than the initial ionization yield (ca. 5 (100 eV) -1 ).…”
Section: Resultsmentioning
confidence: 94%